Pentingnya Pemahaman Sistem Pengendalian Internal dan Bahaya Fraud di Pemerintah Desa Duwet Krajan, Kabupaten Malang - Tomy Rizky Izzalqurny; Fera Pebriyanti; Gusti B’Tari Artichah; Intan Dilla Sabilah; Sayyid Achmad Abdillah (Jumat Ekonomi: Jurnal Pengabdian Masyarakat, 2022)
Village governments are required to implement good government governance. One of the main pillars is accountability in village financial management by reporting village budgets. Through village budget reporting, it is hoped that the tendency of fraud can be avoided. Fraud occurs due to several factors including: apparatus competence, internal control system, morality, organizational culture. The purpose of socialization is to create good village governance and to know the dangers of fraud. The socialization activity was carried out by the service group on January 6 and 12, 2022 which was attended by village apparatus at the Duwet Krajan Village Hall and the Village Head's house. This community service activity in the form of socialization uses several stages of the process to overcome existing problems. The stages carried out are planning, implementation, and evaluation. With this socialization, village apparatus can understand the internal control system to implement in order to achieve good village government governance and prevent fraud.